Endovascular aneurysm sealing: early and midterm results from the EVAS FORWARD Global Registry - Thompson, Matt; Heyligers, Jan M.; Hayes, Paul D.; Reijnen, Michel M. P. J.; Böckler, Dittmar; Schelzig, Hubert; Vries, Jean-Paul P. M. de; Krievins, Dainis; Holden, Andrew (Journal of endovascular therapy, 2016)
Purpose: To report the early and 12-month results of a global registry of patients treated with endovascular aneurysm sealing (EVAS) for abdominal aortic aneury...
Gesehen am 27.05.2020